Fzd7/Wnt7b signaling contributes to stemness and chemoresistance in pancreatic cancer. (2nd May 2021) - Zhang, Zhongbo; Xu, Yuanhong; Zhao, Chenghai
Abstract: Mining databases and data obtained from assays on human specimens had shown that Fzd7 is closely associated with Wnt7b, that Fzd7/Wnt7b expression is upregulated in pancreatic cancer tissues compared with normal tissues, and its expression is negatively correlated with survival. Fzd7/Wnt7b knockdown in Capan‐2 and Panc‐1 cells reduced the proliferative capacity of pancreatic cancer stem cells (PCSCs), reduced drug resistance, decreased the percentage of CD24 + CD44 + subset of cells and the levels of ABCG2, inhibited cell‐sphere formation, and reduced gemcitabine (GEM) resistance. In contrast, Fzd7/Wnt7b overexpression increased the percentage of the CD24 + CD44 + subset of cells, and increased the levels of ABCG2 detected in cell spheroids. The gem‐resistant cells exhibited higher levels of Fzd7/Wnt7b expression, an increased percentage of CD24 + CD44 + cells, and higher levels of ABCG2 compared with the parental cells. Taken together, Fzd7/Wnt7b knockdown can reduce PDAC cell stemness and chemoresistance by reducing the percentage of CSCs. Mechanistically, Fzd7 binds with Wnt7b and modulates the levels of β‐catenin, and they may exert their role via modulation of the canonical Wnt pathway. Abstract : This study aims to elucidate the regulatory mechanism of stemness and chemoresistance in pancreatic cancer, especially the role of Wnt signaling pathway on stemness and chemoresistance of pancreatic cancer. Fzd7/Wnt7b can regulate the proportion of CSC subset, so that they influence stemness and chemoresistance.